2018
DOI: 10.3390/s18082421
|View full text |Cite
|
Sign up to set email alerts
|

A 3-D Meandered Probe-Fed Dual-Band Circularly Polarized Dielectric Resonator Antenna

Abstract: A dual-band circularly polarized (CP) dielectric resonator antenna (DRA) designed on multi-layer substrates is proposed. An asymmetric C-shaped metallic strip is also incorporated into the upper side of the top substrate in the proposed design. The hexagonal dielectric resonator (DR) is excited by the proposed 3-D meandered probe, which generates multiple orthogonal TE-modes. It is found that the lower CP band arises due to the pair of fundamental modes of the hexagonal DR. In the upper CP band, pairs of highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Recently, there is an interest in developing single-point fed dual-band CP DRAs to manage the demands of modern communication systems. Several DRAs have been demonstrated that excite the orthogonal pairs of fundamental and higher-order modes to produce dual-band circular polarization [1][2][3][4][5][6][7][8][9]. For instance, a grooved DR with corner truncation is designed that has a dual-band CP response [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there is an interest in developing single-point fed dual-band CP DRAs to manage the demands of modern communication systems. Several DRAs have been demonstrated that excite the orthogonal pairs of fundamental and higher-order modes to produce dual-band circular polarization [1][2][3][4][5][6][7][8][9]. For instance, a grooved DR with corner truncation is designed that has a dual-band CP response [1].…”
Section: Introductionmentioning
confidence: 99%
“…To cope with the demands of modern communication systems, the single-point fed dual-band CP DRAs have been demonstrated in recent times. One such technique involves the separate excitation of fundamental and higher modes of the DR [ 12 , 13 , 14 , 15 , 16 ]. The other includes the use of hybrid configuration where modes of the DR and coupling slot are separately excited [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%